Road collector drain angle of partially full flow circular curb inlet opening - Dazira Fisha Rajabon, 1993- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia